2015
DOI: 10.1523/jneurosci.3284-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

cJun and CREB2 in the Postsynaptic Neuron Contribute to Persistent Long-Term Facilitation at a Behaviorally Relevant Synapse

Abstract: Basic region leucine zipper (bZIP) transcription factors regulate gene expression critical for long-term synaptic plasticity or neuronal excitability contributing to learning and memory. At sensorimotor synapses of Aplysia, changes in activation or expression of CREB1 and CREB2 in sensory neurons are required for long-term synaptic plasticity. However, it is unknown whether concomitant stimulus-induced changes in expression and activation of bZIP transcription factors in the postsynaptic motor neuron also cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…We have not determined whether the brief training with anisomycin during the inactive phase produces only 24 hr memory, or also a more persistent memory. If the training produces a persistent memory, it could require changes in CREB2 expression 6 hr or more after training, similar to the post-synaptic increases seen by Hu et al (2015) for persistent synaptic plasticity. However, since they found that CREB2 expression decreases presynaptically but increases postsynaptically, examining expression in the whole buccal ganglia might not find these changes, if presynaptic and postsynaptic changes balance one another.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We have not determined whether the brief training with anisomycin during the inactive phase produces only 24 hr memory, or also a more persistent memory. If the training produces a persistent memory, it could require changes in CREB2 expression 6 hr or more after training, similar to the post-synaptic increases seen by Hu et al (2015) for persistent synaptic plasticity. However, since they found that CREB2 expression decreases presynaptically but increases postsynaptically, examining expression in the whole buccal ganglia might not find these changes, if presynaptic and postsynaptic changes balance one another.…”
Section: Discussionmentioning
confidence: 94%
“…It is important to note that CREB2 transcription could still have a major role in the regulation of memory formation in our system. Hu et al (2015) showed that post-synaptic increases in CREB2 and c-jun underlie a persistent increase in synaptic strength, along with presynaptic decreases. In our behavioral paradigm, a full training during the active phase produces separable long-term (24 hr) and persistent (48 hr and longer) memories (Levitan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies target pathways, such as PERK and HRI kinases. Additionally, a recent study on Aplysia sensorimotor long-term facilitation (LTF) provided evidence that LTF in this system requires increased post-synaptic ApCREB2 expression/activity (Hu et al, 2015). Interestingly, elevating ApCREB2 post-synaptically increased synaptic strength while doing this pre-synaptically decreased synaptic strength.…”
Section: Discussionmentioning
confidence: 99%
“…ATF4 plays several critical roles in cellular physiology. For example, ATF4 expression is induced as a component of the integrated stress response (ISR) that regulates cellular amino acid supply, protects against oxidative stress [4], and supports normal postsynaptic function [5,6]. The ISR is implicated in several disease states [7] such as obesity and diabetes [8].…”
Section: Introductionmentioning
confidence: 99%